A study of trucut biopsies of hepatic lesions with special reference to immunohistochemistry and special stain - Venkatesh, Veenaa; Uvaraj, Vinuta; T. M., Karthikeyan (International Journal of Research in Medical Sciences, 2016)
Background: Hepatocellular carcinoma is one of the most common malignancies that account to about half a million deaths yearly and is the third leading cause of death. 80% of these cases are seen in the Asian- Pacific region. Aims of the study were to study the role of immunohistochemistry in differentiating primary from metastatic neoplasms of liver and to evaluate the usefulness of reticulin in differentiating benign from malignant lesions of liver. Methods: 46 cases of hepatic neoplasms reported were taken. Immunohistochemistry was done using the markers Alpha Fetoprotein (AFP), Hep Par 1, Cytokeratin 7 and Cytokeratin 20. Reticulin stain was done in 10 difficult cases to differentiate neoplastic from non-neoplastic lesions of liver. Results: AFP was positive in 18 cases (84%), 20 cases were positive for Hep Par 1 (92%). Among the metastatic neoplasms, the most common expression was cytokeratin 7 positive/ cytokeratin 20 negative expressions which were observed in 54% of cases. Reticulin fibres in the benign processes revealed one-cell thick liver plates, whereas in dysplastic and carcinomatous deposits, they showed thickening of the hepatic cell plates which appeared as two or three cell-cell thick plates. Conclusions: Alpha Fetoprotein and Hep Par 1 are found to be useful in diagnosing hepatocellular carcinomas; and Hep Par 1 is more sensitive than Alpha Fetoprotein. Cytokeratins 7 and 20 were useful in assessing the primary tumour to some extent in case of metastatic carcinomatous deposits of liver. If adequate liver biopsy sample is received, an extended panel of markers can be used to find the site of primary with more accuracy. Reticulin stain can be used in cases where there is difficulty in differentiating neoplastic from non-neoplastic lesions of liver.